Patient perceptions of the benefits and barriers of virtual postnatal care: a qualitative study - Megan Saad; Sophy Chan; Lisa Nguyen; Siddhartha Srivastava; Ramana Appireddy (BMC, 2021)
Abstract Objective The objective of this study is to understand the perceptions of new mothers using virtual care via video conferencing to gain insight into the benefits and barriers of virtual care for obstetric patients. Methods Semi-structured interviews were conducted with 15 patients attending the Kingston Health Sciences Centre. The interviews were 20-25 min in length and recorded through an audio recorder. Thematic analysis was conducted in order to derive the major themes explored in this study. Results New mothers must often adopt new routines to balance their needs and their child's needs. These routines could impact compliance and motivation to attend follow-up care. In our study, participants expressed high satisfaction with virtual care, emphasizing benefits related to comfort, convenience, communication, socioeconomic factors, and the ease of technology use. Participants also perceived that they could receive emotional support and build trust with their health care providers despite the remote nature of their care. Due to its ease of use and increased accessibility, we argue that virtual care shows promise to facilitate long-term compliance to care in obstetric patients. Conclusions Virtual care is a useful modality that could improve compliance to obstetric care. Further research and clinical endeavours should examine how social factors and determinants intersect to determine how they underpin patient perceptions of virtual and in-person care.